2006
DOI: 10.1007/s00440-006-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

A random environment for linearly edge-reinforced random walks on infinite graphs

Abstract: We consider linearly edge-reinforced random walk on an arbitrary locally finite connected graph. It is shown that the process has the same distribution as a random walk in a time-independent random environment given by strictly positive weights on the edges. Furthermore, we prove bounds for the random environment, uniform, among others, in the size of the graph. 34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 7 publications
0
27
1
Order By: Relevance
“…Although (X t ) t∈N 0 is not a Markov chain, it was shown in [8] that the edge-reinforced random walk is recurrent if and only if it returns to the starting point at least once with probability one.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Although (X t ) t∈N 0 is not a Markov chain, it was shown in [8] that the edge-reinforced random walk is recurrent if and only if it returns to the starting point at least once with probability one.…”
Section: Resultsmentioning
confidence: 98%
“…In [8], it is shown that the edge-reinforced random walk on any graph with arbitrary initial weights has the same distribution as a mixture of reversible Markov chains. For the periodic graphs defined above with periodic initial weights, we can say more: Denote by := (0, ∞) E the set of strictly positive edge weights for the graph G. For x = (x e ) e∈E ∈ , set…”
Section: Theorem 21 (Recurrence) the Edge-reinforced Random Walk On mentioning
confidence: 98%
See 3 more Smart Citations